Centrifugally spun poly(ethylene oxide) fibers rival the properties of electrospun fibers. Issue 22 (17th August 2021) - Merchiers, Jorgo; Martínez Narváez, Carina D. V.; Slykas, Cheryl; Buntinx, Mieke; Deferme, Wim; D'Haen, Jan; Peeters, Roos; Sharma, Vivek; Reddy, Naveen K.
Abstract: Centrifugal force spinning (CFS), also known as centrifugal spinning, forcespinning, or rotary jet spinning, provides considerably higher production rates than electrospinning (ES), but the more widespread use of CFS as an alternative depends on the ability to produce fibers with robust thermal and mechanical properties. Here, we report the CFS of poly(ethylene oxide) (PEO) fibers made using a spinning dope formulated with acetonitrile (AcN) as the volatile solvent, and we describe the thermal and mechanical properties of the centrifugally‐spun fibers. Even though the formation, diameter, and morphology of electrospun and centrifugally‐spun PEO fibers are relatively well‐studied, the article presents three crucial contributions: the pioneering use of PEO solutions in AcN as spinning dope, characterization of crystallinity and mechanical properties of the centrifugally‐spun PEO fibers, and a comparison with the corresponding properties of electrospun fibers. We find that fiber formation occurrs for the chosen CFS conditions if polymer concentration exceeds the entanglement concentration, determined from the measured specific viscosity. Most significantly, the centrifugally spun PEO fibers display crystallinity, modulus, elongation‐at‐break, and fiber diameter that rival the properties of electrospun PEO fibers reported in the literature. Abstract :